MINANGKABAU TRADITIONAL THEATER IN THE FRAMEWORK OF DISCOURSE STUDIES - Maryelliwati, Maryelliwati; Rahmad, Hari Adi; Charaka, Kenji Putra (Journal of Pragmatics and Discourse Research, 2022)
Basically, a theater script is a disclosure of life through the form of language.  This study will look at how the Minangkabau traditional theater analyzed the frame of discourse studies and raised its moral message. The method is qualitative analysis with literature and field research. From the results of literature and field found that discourse that appears in theater scripts such as ceremonies, rituals, stories, or entertainment is an act of speech or events. As a cultural index, the language in the Minangkabau theater script also reveals the way of thinking and organizing the experience of its speakers which in certain fields appear in lexical items and as symbolic language culture indicates ethnic cultural identity.